2019
DOI: 10.3390/en12040755
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of Turboexpander Application at Natural Gas Regulation Stations

Abstract: During the natural gas pipeline transportation process, gas stream pressure is reduced at natural gas regulation stations (GRS). Natural gas pressure reduction is accompanied by energy dissipation which results in irreversible exergy losses in the gas stream. Energy loss depends on the thermodynamic parameters of the natural gas stream on inlet and outlet gas pressure regulation and metering stations. Recovered energy can be used for electricity generation when the pressure regulator is replaced with an expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Kuczyński et al [115] focused on energy recovery in natural gas regulation stations by using suitable turboexpanders. In fact, natural gas regulation stations feature a significant energy dissipation, due to dissipative pressure reduction.…”
Section: Energy Efficiency In Industrymentioning
confidence: 99%
“…Kuczyński et al [115] focused on energy recovery in natural gas regulation stations by using suitable turboexpanders. In fact, natural gas regulation stations feature a significant energy dissipation, due to dissipative pressure reduction.…”
Section: Energy Efficiency In Industrymentioning
confidence: 99%
“…[15][16] Kuczynski et al presented formula that allows a quick and easy evaluation of the applicability of an expander on the selected gas regulation station. 17 Olfati et al 18 presented the energy and exergy analyses of a pressure reduction station. They investigated various operating conditions for station inlet pressure and temperature and the modification on preheating natural gas was considered.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, natural gas is transported at high pressure (40-100 bar) in pipelines but its pressure needs to be reduced (2-20 bar) for delivery in the Gas Regulation Stations (GRS) by means of valves. However, Kuczyński et al [2] shown that GRS are characterized by a wide range of parameters (e.g., pressure drop) and only some of them are suitable to replace the throttling valves with the turboexpander. Furthermore, boundary conditions such as irregular daily and seasonal temperatures make stringent conditions in using the turboexpander.…”
Section: Introductionmentioning
confidence: 99%